What is small? Small and medium enterprises facing patenting activities - Abraham Garcia; Dominique Foray (European Commission, Joint Research Centre (JRC), 2010)
The effect of a firm's size is analysed in relation with the probability of applying for a patent. We worked on the identification of a firm's minimum size, a threshold needed to formally protect an innovation by legal means. Below this minimum size the costs associated with protection are so high that firms prefer informal protection of their innovations. The literature concludes that as size increases so does the propensity to patent. This research finds similar results for pool regressions. In an attempt to understand the relationship between size and patent activity better, the population of firms is divided into two groups. On a first stage a firm was considered small if it had below 250 employees and large if it had more; a moving threshold was applied on a second stage. The results show that for some economies the minimum threshold needed for filing a patent is well below 250 employees.
Keywords: O31; O34; C01; 330; SME; patents; IPRs